Analisis Preferensi Nasabah dalam Pemanfaatan Produk Funding Bank Syariah Mandiri Kantor Cabang Bogor (Jurnal Sosial Humaniora dan Pendidikan, 2022)
In the products of Bank Syariah Mandiri, the Bogor branch office is often referred to as funding or fundraising, namely BSM Savings products, BSM Giro products, and BSM Bank Syariah Mandiri Time Deposit products, Bogor branch offices have good potential to attract new customers with the support of modern technological developments owned by Bank Syariah Mandiri Bogor branch office. This study agreed to determine customer preferences in the use of funding products to increase the collection of BSM Savings, BSM Current Accounts, and BSM Time Deposits from customers and the impact of using funding products in increasing customer interest in raising funds for Bank Syariah Mandiri Bogor branch offices. In this study using primary data from direct BSM customers with a total of 36 respondents for data collection using a structured questionnaire distribution carried out with google From for one week starting from 7 June to 14 June 2020 for research methods using descriptive and data processing using frequency calculations to determine the number the percentage of Very Like and Very Dislike. In the product funding of Bank Syariah Mandiri branch offices in Bogor, it can be seen that the percentage results of this researcher show that the dominant customer really likes BSM Savings products because customers really like the BSM Savings product as a place to store money in accordance with sharia regulations and can be retrieved when the customer needs it. for the second, based on the percentage of dominant customers in BSM Deposit products because customers want to invest their funds to be collected again by the Bogor branch office of Bank Syariah Mandiri and get aprofit impact with a profit sharing system in accordance with sharia provisions and the third there are some dominant customers who really like to use checks or Bilyet Giro to make transactions easier and save time without spending a lot of money on transactions.